An eco-driving strategy for an electric bus: insert permanent magnet synchronous motor (IPMSM) drivetrain - Jele, Mjozi Robson (My University, 2022)
There has been a growing interest in adopting electric vehicles (EVs) over internal combustion engine (ICE) vehicles. However, there are a number of challenges to the adoption of EVs. Firstly, they suffer from low mileage coverage due to poor speci c energy in batteries. Secondly, there is a de cit in electric vehicle charging infrastructure and, thirdly, the current battery technology has low charging rates (C-rate). These concerns makes EV to be undesirable as compared to ICE vehicles since gasoline and diesel have high speci c energy as compared to batteries. Therefore, it becomes extremely imperative that the onboard nite energy must be used optimally during a driving schedule. This research is concerned with the further development and simulation of an eco-driving strategy for an electric vehicle. This strategy makes use of the vehicle's technical parameters, road gradient, and the electric traction machine effciency map. A Matlab/Simulink EV model based on an existing EV of the Technical University of Munich (TUM) was developed and validated. The EV model is based on an insert permanent magnet synchronous motor (IPMSM) drivetrain. The EV model was used to develop and validate the eco-driving strategy. An error of 1.8% in terms of energy consumption for a test drive cycle was observed between the Simulink EV model and TUM EV. Firstly, the TUM EV eco-driving strategy is further developed and simulated by the Simulink EV model. Secondly, the TUM EV is test-driven according to the Simulink EV model simulations. The TUM EV was found to have an optimal speed of 24km/hr for a zero gradient drive route and an error between the energy consumption rates of the Simulink EV model and TUM EV was found to be 1.93%. The TUM EV is found to have an energy saving of 31.2% when driving using the eco-driving strategy. For an acceleration from zero to 24km/hr, the as-fast-as-possible acceleration architecture ( = 0:4) is found to be 33.33% more efficient as compared to the as-slow-as-possible mode ( = 4). The eco-drive strategy saves 8.7% for a distance of 550m with a road gradient of 0.076 as compared to conventional driving of an urban eBus. The eco-driving strategy can be applied to any electric vehicle and can be used in conjunction with a GPS navigation system. It can be offered by electric vehicle manufacturers for optimal use of nite battery energy.
A dissertation submitted to the Faculty of Engineering and Built Environment, University of the Witwatersrand, in partial ful llment of the requirements for the degree of Master of Science in Engineering, 2022